TINGKAT KEPARAHAN STAIN AKIBAT MENGONSUMSI KOPI PADA ORANG DEWASA DI CILINCING JAKARTA UTARA - awal ramadan, azrul (THERA-DENT (jurnal terapis gigi dan mulut), 2023)
Background: A smile is a small thing that has a very big impact on appearance and also plays an important role in influencing the beauty of a smile, namely teeth. Coffee is one of the most popular drinks for many people. Tooth stain is a color that sticks to the surface of the teeth usually occurs due to the attachment of the color of food, drink. Purpose: To determine the severity of stains due to coffee consumption in adults in Cilincing, North Jakarta. Research method: This research design uses quantitative research with a population of 50 and a sample of 40 people. Research results : from 40 respondents the severity of coffee consumption on stain formation, 28 people had good criteria, 12 had moderate criteria. Conclusion : There is an effect of coffee consumption frequency on stain formation and age has no effect on stain formation.